Synovial cyst of the temporomandibular joint: a case report with surgical management and long‐term follow‐up. (26th November 2014) - Verma, S.; Chambers, I.
Abstract Synovial cysts of the temporomandibular joint (TMJ) are rare, with only 10 cases reported in the literature. They may present with pain, swelling or trismus and can be a diagnostic dilemma for the clinician. With reference to the literature, this case report describes the presentation, investigation and management of a rare synovial cyst of the TMJ, presenting as a painful preauricular swelling in a 33‐year‐old woman. The long‐term follow‐up of this patient is discussed. We explore different modes of imaging of such disorders, as well as the histological features and the reported treatment modalities of temporomandibular synovial cysts.